Retrospective Study of Clinical Characteristics, Natural History and Predictive Factors for Mild Autonomous Cortisol Secretion (MACS) in Patients with Adrenal Incidentalomas in Malaysia - Devaraja, Vanusha; Rajoo, Subashini; Valayatham, Vijaya Mala; Hui, Foo Siew (Journal of the ASEAN Federation of Endocrine Societies, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:cbbf575c-7dcb-43e6-a391-4d0dc3abf94e-5" data-testid="conversation-turn-12" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="eaf87e8a-67a5-46c3-b811-6c5b2cd84ff4" data-message-model-slug="gpt-5-3" data-turn-start-message="true"> Introduction. Adrenal incidentalomas (AIs) are frequently discovered during imaging performed for unrelated conditions. While most are benign and non-functional, a subset demonstrates hormonal activity or malignant potential. This study aimed to describe the clinical and radiological characteristics, natural history and predictors of mild autonomous cortisol secretion (MACS) in a Malaysian cohort. Methodology. This retrospective multicentre study reviewed medical records of 251 patients with AIs from three tertiary hospitals in Malaysia. Data on demographics, imaging findings, hormonal evaluations, histopathological diagnoses and longitudinal follow-up, including serial imaging and hormonal assessments, were collected and analysed. Results. The median age of the cohort was 58 years (IQR 19), with a slight female predominance (53%). The population was predominantly Malay (n = 126, 50.2%), followed by Chinese (36.3%) and Indian (12.7%). The median follow-up duration was 39 months. Most AIs were non-malignant (92%) and non-functioning (72%). Bilateral lesions were present in 9.6% of patients. Among non-malignant AIs, 27% were functioning, with higher rates of hypertension and osteoporosis, larger tumour size and greater tumour density. Adrenalectomy was more commonly performed in the functioning group, mainly for MACS and pheochromocytoma. In contrast, 94% of benign non-functioning AIs were managed conservatively, with no cases of malignant transformation and only one case developing hormonal activity over a median follow-up of 30 months. Among the 20 malignant AIs, 12 were primary adrenal carcinomas. Malignant AIs were associated with larger size, overt Cushing’s syndrome, higher Hounsfield units, lower contrast washout and increased mortality. MACS was identified in 12.7% of the cohort. It was associated with bilateral lesions, larger tumour size, and higher prevalence of diabetes, dyslipidaemia, obesity and osteoporosis. On multivariate analysis, only bilaterality and osteoporosis remained significant predictors of MACS. Conclusion. This study reinforces that most benign non-functioning AIs carry minimal risk of progression, supporting less intensive follow-up in stable cases. Bilaterality and osteoporosis were identified as independent predictors of MACS, emphasizing the importance of targeted hormonal and bone health monitoring in these patients.